The Comparison of Commisive Speech Acts by Trump and Warren Presidential Candidate Viewed from Gender Differences - Nabila, Zulfa; Mujiyanto, Januarius; Rukmini, Dwi (English Education Journal, 2021)
Politics is not only controlled by male but also female. Commissive speech acts often happen in presidential campaign speeches. This research aims to analyze the comparison of commissive speech acts in English speeches by Trump and Warren presidential candidate viewed from gender differences. Qualitative method is applied in this research. The data are analyzed by using commissive speech acts from Searle (2005), Cutting (2002) and talk theory from Tannen (1991). The findings show that Trump used seven types of commissive: promise, guarantee, pledge, contract, offering, threaten, and refusal. The functions are giving solution, convincing, insulting, threatening, showing care, and encouraging. Warren used three types of commissive: promise, guarantee, and threaten. The functions are giving solution, convincing, threatening, and showing care. There are three similarities of commissive between them: promise, guarantee, and threaten. Promise is the most frequent type used by them. Viewed from gender differences, female and male presidential candidates applied report and raport talks. They tended to use report talks.The differences are that Trump employed more types of commissive than Warren did. Trump used seven types while Warren used three. Viewed from gender differences, Trump’s report talk is more varied than Warren’s. Meanwhile, Warren’s rapport talk is more varied than Trump. This research gives the example to students of English language on how to convince hearers or audience by utilizing commissive speech acts.